An Exploration of the Experiences of Physical Therapists Who Identify as LGBTQIA+: Navigating Sexual Orientation and Gender Identity in Clinical, Academic, and Professional Roles. Issue 3 (22nd December 2021) - Ross, Megan H; Hammond, John; Bezner, Janet; Brown, Darren; Wright, Andrea; Chipchase, Lucy; Miciak, Maxi; Whittaker, Jackie L; Setchell, Jenny
Abstract: Objective: The purpose of this study was to explore physical therapy through the stories of physical therapists who identify as lesbian, gay, bisexual, transgender, queer, intersex, asexual, and other related identities (LGBTQIA+) to consider how the profession enacts and constructs gender and sexual orientation. Methods: Physical therapists with clinical, academic, and professional roles who identify as LGBTQIA+ were recruited from Australia, the United Kingdom, Canada, and the United States. In-depth data were collected via narrative interviews. An iterative group discourse analysis was used to examine key discourses underpinning interview narratives and how these relate to the physical therapy profession. Results: Twenty-two physical therapists were interviewed. Participants had between 1.5 and 40 years of experience across various clinical areas and settings. Participants identified with varying sexual orientations and gender identities. Analysis identified discourses discussed under the following headings: (1) normativity, which related to hetero-normative assumptions about sexual orientation and cisnormative assumptions about gender identity and the intersectionality among sexual orientation, gender identity, and other forms of marginalization; (2) stress and labor, which explored the stress experienced by physical therapists who are LGBTQIA+ (due to fear of discrimination or actual discrimination) and additional emotional and other types of labor or work done in the workplace to hide aspects of their lives to feel safe, educate colleagues, and be a role model; and (3) professionalism, which related to the heterosexual/cisnormative (and other) "norms" that comprised participants' ideas of presenting as "professional" and positioning physical therapists who are LGBTQIA+ as "unprofessional." Conclusion: Findings suggest that cultural norms may need to be reconceptualized in physical therapy to promote inclusion and belonging of individuals who identify as LGBTQIA+. Approaches to upskill new and existing physical therapists may include elements such as individual and institutional reflexivity, learning and implementing appropriate terminology, displaying indicators of inclusivity, and cultural safety training. These elements may provide the first steps to promote inclusive and culturally safe environments for individuals who identify as LGBTQIA+ within the profession. Impact: This is the first known study to explore the lived experiences of those who identify as LGBTQIA+ in the physical therapy profession. The findings highlight how prevailing normative discourses in Western society are also present in physical therapy and impact those who identify as LGBTQIA+.